Peran Lingkungan Sosial Terhadap Kontrol Diri Kaum Milenial - Asmuni, Hadiqoh (Pendidikan Agama Islam, 2019)
The social environment is a place where every individual can carry out daily activities, both within the family environment, school environment, and community environment. The role of the environment as a place of daily interaction in society as a determinant of one's personal development in a society full of diversity and the factors that underlie interaction for millennials. With a good environment it will print a good generation too. One way is through education and collecting positive information. This is a solution for millennials in controlling themselves so they can control themselves so that they will act positively in thinking. Millennials must be able to control themselves by sorting and choosing useful values ??through the use of technology and extracting information from the internet and social media and finding good partners in socializing in the surrounding environment. So that millennials are more flexible in adapting to any changes that occur.